Copy number variants underlie major selective sweeps in insecticide resistance genes in Anopheles arabiensis. - Eric R Lucas; Sanjay C Nagi; Bilali Kabula; Bernard Batengana; William Kisinza; Alexander Egyir-Yawson; John Essandoh; Sam Dadzie; Joseph Chabi; Arjen E Van't Hof; Emily J Rippon; Dimitra Pipini; et al. (PLoS Biology, 2024)
To keep ahead of the evolution of resistance to insecticides in mosquitoes, national malaria control programmes must make use of a range of insecticides, both old and new, while monitoring resistance mechanisms. The outdoor-biting malaria vector Anopheles arabiensis is of increasing concern for malaria transmission because it is apparently less susceptible to many indoor control interventions, yet knowledge of its mechanisms of resistance remains limited. Furthermore, comparatively little is known in general about resistance to non-pyrethroid insecticides such as pirimiphos-methyl (PM), which are crucial for effective control in the context of globally high resistance to pyrethroids. We performed a genome-wide association study to determine the molecular mechanisms of resistance to the pyrethroid deltamethrin (commonly used in bednets) and PM (widespread use for indoor spraying), in An. arabiensis from 2 regions in Tanzania. Genomic regions of positive selection in these populations were largely driven by copy number variants (CNVs) in gene families involved in metabolic resistance. We found evidence of a new gene cluster involved in resistance to PM, identifying a strong selective sweep tied to a CNV in the carboxylesterase genes Coeae2g - Coeae6g. Using complementary data from another malaria vector, An. coluzzii, in Ghana, we show that copy number at this locus is significantly associated with PM resistance. Similarly, for deltamethrin, resistance was strongly associated with a novel CNV allele in the Cyp6aa / Cyp6p cluster (Cyp6aap_Dup33). Against this background of metabolic resistance, resistance caused by mutations in the insecticide target sites was very rare or absent. Mutations in the pyrethroid target site Vgsc were at very low frequency in Tanzania, yet combining these samples with 3 An. arabiensis individuals from West Africa revealed a startling evolutionary diversity, with up to 5 independent origins of Vgsc-995 mutations found within just 8 haplotypes. Thus, despite having been first recorded over 10 years ago, Vgsc resistance mutations in Tanzanian An. arabiensis have remained at stable low frequencies. Overall, our results provide a new copy number marker for monitoring resistance to PM in malaria mosquitoes, and reveal the complex picture of resistance patterns in An. arabiensis.